1991
DOI: 10.1103/physreva.44.5122
|View full text |Cite
|
Sign up to set email alerts
|

Fluid hydrogen at high density: Pressure dissociation

Abstract: We develop a model for the Helmholtz free energy of fluid hydrogen at high density and high temperature. This model aims at describing both pressure and temperature dissociation and ionization and bears directly on equations of state of partially ionized plasmas, as encountered in astrophysical situations and high-pressure experiments. This paper focuses on a mixture of hydrogen atoms and molecules and is devoted to the study of the phenomenon of pressure dissociation at finite temperatures. In the present mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 61 publications
(108 reference statements)
7
120
0
1
Order By: Relevance
“…4). Sophisticated EOSs, including collective effects, have been designed to study the Sun (MHD EOS, Mihalas et al 1988; OPAL EOS, Rogers et al 1996) and very-low mass stars and planets (as the SC EOS, Saumon & Chabrier 1991). The effects of the EOS on the models are illustrated in Fig.…”
Section: Equation Of Statementioning
confidence: 99%
“…4). Sophisticated EOSs, including collective effects, have been designed to study the Sun (MHD EOS, Mihalas et al 1988; OPAL EOS, Rogers et al 1996) and very-low mass stars and planets (as the SC EOS, Saumon & Chabrier 1991). The effects of the EOS on the models are illustrated in Fig.…”
Section: Equation Of Statementioning
confidence: 99%
“…This potential is slighly softer than the potential used in our calculations (Ross et al 1983;Saumon and Chabrier 1991). Given the lack of information for the H-H and H2-H potentials at high density, we mimicked many-body effects by softening arbitrarily the repulsive part of the potentials respectively by 20% and 35%.…”
Section: Softening Of the Potentialmentioning
confidence: 99%
“…In section II, we give a short presentation of our free energy model, which has been presented extensively elsewhere (Saumon and Chabrier 1991, 1992). In section III, we discuss in detail the P P T predicted by our model whereas a comparison with other models is discussed in Section IV.…”
Section: Introductionmentioning
confidence: 99%
“…The equation of state (EOS) along the principal Hugoniot was determined by Nellis, et al (1), and theoretical models were developed subsequently. (2,3) Recently, new shock temperature measurements led to the development of a new model, in which the effective molecular dissociation energy decreases with decreasing volume. (4) Extrapolation of those results to pressures above 100 GPa indicated that deuterium would be substantially more compressible in this pressure region than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the measurement of derivative quantities such as sound velocity or the Grüneisen parameter, both of which should be sensitive to the to the rate of change of compressibility. The sound velocity c of a rarefaction wave is given by (1) where P is pressure, ρ density, and the derivative is at constant entropy S. The sound velocity is also related to the Grüneisen parameter through the expression (7) (2) where the Grüneisen parameter given by (3) can be obtained from shock Hugoniot experiments. Measurements of the sound velocity using the overtake method (8) can provide high accuracy, and an unambiguous test of our understanding of dense, hot, fluid deuterium.…”
Section: Introductionmentioning
confidence: 99%